PSIKOEDUKASI EMPATI “TEPA SLIRA” SEBAGAI UPAYA PENCEGAHAN PERILAKU BULLYING PADA ANAK SEJAK EARLY CHILDHOOD - Dina Pratiwi Primadiaty; Fadila Sofiana; Benita Khansarisky; Annastasia Ediati (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The phenomenon of bullying has recently been in the spotlight of Indonesian society. Bullying behavior will hinder children's growth in developing empathy and compassion for others. This research aims to determine the effect of empathy psychoeducation